Microtubule Cytoskeleton and Spermatogenesis—Lesson From Studies of Toxicant Models. (9th July 2020) - Wang, Lingling; Yan, Ming; Wu, Siwen; Mao, Baiping; Wong, Chris K C; Ge, Renshan; Sun, Fei; Cheng, C Yan
Abstract: Studies have shown that mammalian testes, in particular the Sertoli cells, are highly susceptible to exposure of environmental toxicants, such as cadmium, perfluorooctanesulfonate, phthalates, 2, 5-hexanedione and bisphenol A. However, important studies conducted by reproductive toxicologists and/or biologists in the past have been treated as toxicology reports per se. Yet, many of these studies provided important mechanistic insights on the toxicant-induced testis injury and reproductive dysfunction, relevant to the biology of the testis and spermatogenesis. Furthermore, recent studies have shown that findings obtained from toxicant models are exceedingly helpful tools to unravel the biology of testis function in particular spermatogenesis, including specific cellular events associated with spermatid transport to support spermiogenesis and spermiation. In this review, we critically evaluate some recent data, focusing primarily on the molecular structure and role of microtubules in cellular function, illustrating the importance of toxicant models to unravel the biology of microtubule cytoskeleton in supporting spermatogenesis, well beyond information on toxicology. These findings have opened up some potential areas of research which should be carefully evaluated in the years to come.